Pengaruh Pemberian Tetraselmis chuii dan Skeletonema costatum Dengan Dosis Yang Berbeda Terhadap Profil Asam Lemak Tidak Jenuh Pada Kerang TOTOK Polymesoda erosa - Hendartono, Nugroho; Trianto, Agus; Supriyantini, Endang (977-2407769)
The study was conducted to determine the effect of various combinations of natural feed T. chuii and S. costatum to the appearance of unsaturated fatty acids Totok clams P. erosa. Implications of the results of this study can be used as the basis in effort Totok clams seed supply in the cultivation of shellfish. Species used in this study Totok sized clams 4-5 cm obtained from the waters around the island Gombol Segara Anakan, Cilacap. The vessel used is a aquarium size of 30 x 30 x 30 cm with 2 individuals/ aquarium with 2 L volumes of media. The method used is an experimental laboratory with a completely randomized design, two factors, there treatments and there replication. Influence of mixture T1 : T. chuii 36 x 104 sel / mL and S. costatum 9 x 104 sel / mL; T2 : T. chuii 27 x 104 sel / mL and S. costatum 18 x 104 sel / mL; T3 : T. chuii 18 x 104 sel / mL and S. costatum 27 x 104 sel / mL. The feed is given once for there months. Measurement of unsaturated fatty acid content using GC-MS method. The results showed that feeding a mixture of T. chuii and S. costatum and maintenance time of real influence (P <0.05) on levels of unsaturated fatty acids Totok P.erosa shells. Formulation of feed mixture with chuii 27 x 104 sel / mL and S. costatum 18 x 104 sel / mL to give better results than the other feed.